(untitled) (Journal of Pure & Applied Sciences, 2019)
The interaction of Co (II), Ni (II) and Cu (II) metal ions and the biologically important amino acid L-Valine, (2-amino-3-methyl butanoic acid) have been investigated. The potentiometric technique was used to study these intraction at 313.15 ± 0.1 K in the absence and in the presence of ionic strength of 0.1 M (NaCl) in aqueous medium. The data obtained under the above experimental conditions were used to evaluate the values of proton-ligand and metal-ligand stability constants using Irving-Rossotti titration technique. The formation of the 1:2, (M:L), binary complexes are confirmed by the corresponding pH titration curves. The values of logK and log? were calculated and found in the order of copper (II) > nickel (II) > cobalt (II).